2007
DOI: 10.1186/1743-8462-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Targeting services to reduce social inequalities in utilisation: an analysis of breast cancer screening in New South Wales

Abstract: Background: Many jurisdictions have used public funding of health care to reduce or remove price at the point of delivery of services. Whilst this reduces an important barrier to accessing care, it does nothing to discriminate between groups considered to have greater or fewer needs. In this paper, we consider whether active targeted recruitment, in addition to offering a 'free' service, is associated with a reduction in social inequalities in self-reported utilization of the breast screening services in NSW, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Among men, having a PSA test alone was associated most strongly with age, family history of prostate cancer, having private health insurance, and being treated by a doctor in the past month, whereas having a FOBT alone was associated most strongly with higher income, living in outer regional areas and being retired. The factors included in our analysis were factors that have been found to be associated with cancer screening in the past [11,14-19], and indeed, all these factors were significantly related to cancer screening in our study. Only one other study has directly compared cancer screening modalities in Australia and that study, restricted to men, also found that PSA testing was more common than bowel screening and that having private health insurance, living with a partner and being white and older were associated with any screening [26].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Among men, having a PSA test alone was associated most strongly with age, family history of prostate cancer, having private health insurance, and being treated by a doctor in the past month, whereas having a FOBT alone was associated most strongly with higher income, living in outer regional areas and being retired. The factors included in our analysis were factors that have been found to be associated with cancer screening in the past [11,14-19], and indeed, all these factors were significantly related to cancer screening in our study. Only one other study has directly compared cancer screening modalities in Australia and that study, restricted to men, also found that PSA testing was more common than bowel screening and that having private health insurance, living with a partner and being white and older were associated with any screening [26].…”
Section: Discussionsupporting
confidence: 54%
“…However, screening mammograms are also commonly accessed through the private sector on a user-pays basis and so the participation rate is more likely to be around 75% [10,11]. In the bowel cancer screening program the participation rate among those invited is around 38.4% (currently only people turning 50, 55 and 65 are invited via a mailed, faecal occult blood test; FOBT) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small differences existed in the timing and methods of screening, for example most countries employed an annual or biennial invitation, except the UK where women were invited every 3 years, and there was variation in the use of digital mammography and clinical breast examination (Dowling et al , 2010). Overall however, by 2004–5 the uptake of screening was consistently 65–75% of eligible women in the UK, Norway, Sweden (Dowling et al , 2010), New South Wales (Birch et al , 2007), British Colombia and Manitoba (Public Health Agency of Canada, 2012). Among these jurisdictions we do not consider that small differences in the screening programmes explain differences in the stage distribution or in stage-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…18 In Spain, previous studies have shown that more than 50% of Pap tests are carried out in the public primary health-care centres, without any cost to the user. 25 This suggests that the annual repetition of the test is not only related to economic incentives, but probably also to the health professional's recommendation.…”
Section: Discussionmentioning
confidence: 99%